IMPLIKASI RETURN ON EQUITY (ROE) DALAM MEMBANGUN KINERJA PERUSAHAAN YANG BERKELANJUTAN - Wairisal, Pulus L (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This study uses a literature study method to understand and analyze the implications of Return on Equity (ROE) on sustainable company performance and identify factors that affect ROE in the context of company performance. The purpose of this study is to provide a comprehensive view of how ROE can be used as an indicator of the effectiveness of a company's performance as well as provide information on the factors that affect the ROE value. The results show that a high and stable ROE is generally associated with excellent company performance, indicating sustainability in shareholder equity management and operational efficiency. The study also revealed that net profit margin, asset turnover, and capital structure are the main factors that affect ROE. The identification of these factors helps companies in designing strategies to improve sustainable financial performance. These findings provide insights for managers to focus more on operational efficiency, asset management, and prudent funding policies in an effort to improve ROe and overall company performance.